Evolving computability : 11th Conference on Computability in Europe, CiE 2015, Bucharest, Romania, June 29-July 3, 2015. Proceedings /: 11th Conference on Computability in Europe, CiE 2015, Bucharest, Romania, June 29-July 3, 2015. Proceedings. (2015) - Unknown
No abstract available